Combination of acquired von Willebrand syndrome (AVWS) and Glanzmann thrombasthenia in monoclonal gammopathy of uncertain significance (MGUS), a case report. Issue 1 (December 2018) - Mayne, Elizabeth; Tait, Malcolm; Jacobson, Barry; Pillay, Evashin; Louw, Susan
Abstract Background Autoimmune paraphenomena, are associated with B-cell lymphoproliferative disorders, including monoclonal gammopathy of uncertain significance. These paraphenomena can rarely include acquired bleeding disorders. Case presentation This case study reports an unusual clinical presentation of 2 acquired bleeding disorders, Acquired von Willebrand syndrome (disease) and Acquired Glanzmann's thrombasthenia, in an elderly patient with monoclonal gammopathy of uncertain significance. Conclusions Acquired bleeding disorders are often underdiagnosed and a high degree of clinical suspicion is required. The patient in this study demonstrated platelet aggregometry which was atypical for isolated Glanzmann's thrombosthenia because of the severe concomitant endogenous decrease in von Willebrand factor. There was an absence of platelet aggregation to all tested agonists including ristocetin. Once the diagnosis was made, however, the patient showed a partial response to intravenous immunoglobulin confirming the immunological pathogenesis in this case. This case highlights the need to consider acquired bleeding disorders in patients with a possible predisposing factor.